Promising Leuce poplar clones in sandy ridges between the rivers Danube and Tisza in Hungary: a case study - Rédei, Károly; Takács, Marianna; Kiss, Tamás; Keserű, Zsolt (Acta Agraria Debreceniensis, 2019)
An intensive integrated research and development work has been carried out on the improvement of Leuce poplars including primarily the native white poplar (Populus alba L.) and its natural hybrid grey poplar (Populus × canescens). More than 70 percent of the Leuce poplar stands can be found on calcareous sandy sites in the Danube–Tisza region, so they play a significant role in the poplar management of this part of the country. The most important task ahead of Hungarian poplar growers is to improve the quality of poplar stands and plantations based on selecting new clones and cultivars. The growth and yield of four promising Leuce poplar clones was evaluated on a marginal site in central Hungary. The clones ‘H 425-4’ (Populus alba L. × Populus alba L.), and ‘H 758’ (Populus alba L. Mosonmagyaróvár 124) seem to be suitable for wood production, while the ‘H 427-3’ (Populus alba L. × Populus alba L. cv. Bolleana) and ‘H 422-9’ (Populus alba L. × Populus grandidentata (Michx)) clones (with decorative stem form) could be better used for tree lines and ornamental plantations.